E3 ubiquitin ligase NEDD4L negatively regulates keratinocyte hyperplasia by promoting GP130 degradation. (26th March 2021) - Liu, Huan; Lin, Wenlong; Liu, Zhiyong; Song, Yinjing; Cheng, Hao; An, Huazhang; Wang, Xiaojian
Abstract: Psoriasis is mainly characterized by abnormal hyperplasia of keratinocytes and immune cells infiltrating into the dermis and epidermis. Neural precursor cell expressed developmentally downregulated 4‐like (NEDD4L) is a highly conserved HECT type E3 ligase that plays an important role in regulating physiological and pathological processes. Here, we identify NEDD4L as a negative regulator of psoriasis. Nedd4l significantly inhibits imiquimod (IMQ)‐induced skin hyperplasia, and this effect is attributed to the inhibitory effect of NEDD4L on IL‐6/GP130 signaling in keratinocytes. Mechanistically, NEDD4L directly interacts with GP130 and mediates its Lys‐27‐linked ubiquitination and proteasomal degradation. Moreover, the expression of NEDD4L is downregulated in the epidermis from IMQ‐treated mice and psoriasis patients and negatively correlates with the protein levels of GP130 and p‐STAT3 in clinical samples. Collectively, we uncover an inhibitory role of NEDD4L in the pathogenesis of psoriasis and suggest a new therapeutic strategy for the treatment of psoriasis. SYNOPSIS: NEDD4L functions as a negative regulator of IL‐6 signaling by inhibiting GP130 expression in keratinocytes. As NEDD4L is downregulated in the epidermis of psoriasis patients, increasing the levels of NEDD4L might be a potential therapeutic strategy for psoriasis. The E3 ubiquitin ligase NEDD4L negatively regulates keratinocyte hyperplasia by inhibiting IL‐6/GP130/STAT3 signaling. NEDD4L directly interacts with GP130 and mediates its Lys‐27‐linked ubiquitination and proteasomal degradation. NEDD4L is reduced in the epidermis of psoriasis patients and negatively correlates with GP130 and p‐STAT3 levels. Abstract : NEDD4L functions as a negative regulator of IL‐6 signaling by inhibiting GP130 expression in keratinocytes. As NEDD4L is downregulated in the epidermis of psoriasis patients, increasing the levels of NEDD4L might be a potential therapeutic strategy for psoriasis.